Examining Classroom Strategies: Reciprocal Teaching and its Effect on Reading Comprehension - Khan, Sadia; Ullah, Saeed; Siraj, Darakhshan; Islam Amjad, Amjad (SAGE open, 2025)
Reading comprehension is one of the significant cognitive abilities that students develop during their early school years. The existing literature supports that explicit reading strategies can improve students’ reading comprehension. The present study investigated the effect of reciprocal teaching on reading comprehension among grade 7 students in English subject. The study is quantitative in nature, and the pretest-posttest nonequivalent control group design (PPNCGD) was used to meet the desired objectives. The sample comprised of 90 students of two intact classes of Grade 7 studying English in a public sector girls’ secondary school. Data were collected using a reading comprehension test (RCT) during pre and post-tests. Using SPSS, we applied independent and paired sample t -tests. Cohen’s d was used to estimate the magnitude of the treatment effect. The results revealed that reciprocal teaching practices have a statistically significant positive effect on the Grade 7 students’ reading comprehension in English. Based on the study’s results, we provided important implications for educators, students and teacher training institutions. How Reciprocal Teaching Improves Reading Comprehension: Evidence from a Classroom Study This study looked at how reciprocal teaching affects reading comprehension in Grade 7 English students. Researchers tested this method in a public girls’ school with 90 students. The study used a pre-test and post-test design to measure improvement. Statistical tests showed that students who experienced reciprocal teaching improved significantly in their reading skills. The study suggests that this approach could help teachers, students, and teacher trainers enhance reading comprehension.